Situation of Souphanouvong University Organizational work and Staff Implementation - SYVAHKHAM, Sengdeuan; KEOBOAULAPHET, Soulideth; PHOMMANIT, Khamson (Souphanouvong University Journal Multidisciplinary Research and Development, 2025)
The purpose of this research is to study the implementation of organizational and personnel work at Souphanouvong University. The sample group consists of 200 employees and teachers from within the university. The research framework is divided into five areas: party-building work, policy work, commendation work, staff management, and staff evaluation. The primary research instrument was a questionnaire based on a 5-point Likert scale. The data were analyzed using frequency, percentage, mean, and standard deviation, with the aid of statistical software. The research findings revealed that the overall implementation of organizational and personnel work at Souphanouvong University was at a high level, with an average score of (X̅ = 3.66, SD = 0.55). When analyzed by individual aspect, party-building work was rated the highest (X̅ = 3.99, SD = 0.56), followed by staff evaluation (X̅ = 3.81, SD = 0.65), staff management (X̅ = 3.67, SD = 0.67), commendation work (X̅ = 3.63, SD = 0.66), and policy work, which received the lowest average rating (X̅ = 3.59, SD = 0.70).